Social and economic impact of «mexico-canadian Seasonal Agricultural Workers» Program, in the community Guadalupe Zaragoza - Lobato Huerta, Sagrario; Duarte, Ángela; Martínez Fernández, Rodolfo; Pezzat Said, Elias B.; Torres, Indiana; Sánchez, Ana (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2013)
In Mexico, Puebla is the third State that sends the highest number of migrant workers to Canada through the Mexican Seasonal Agricultural Workers program (SAWP). Guadalupe Zaragoza, Tlahuapan is the community with the highest rate of participation in the program. According to the Mexican National Counsel of Population, town of Tlahuapan is classified in the poverty category three, where the first three levels represent serious problems of social inequality. Therefore, it was not difficult to anticipate that the most important motivation to emigrate is the lack of employment. Worker´s families face hardship situation while the worker is in Canada. Although they inhabit suitable housing, their health status and their childhood remain vulnerable. Workers’ wives continue unfolding in patriarchal relations, usually work hard —sometimes double shifts— and suffer from subjective symptoms of stress and fatigue. From their total income, each family spend more on education, health and basic services, with up to four times higher than an average family at a national and state level, and allocate a percentage of their family remittances for community use. This community practices cultural consumption of the lower classes. The SAWP workers’ identities have changed in a minimal way; however, migration itself implies a high affective cost for families